Effects of Ellagic Acid upon the Rabbit Fibrinolytic System - Iatridis, S. G; Iatridis, P. G (Thrombosis and Haemostasis, 1972)
The present investigation deals with in vivo studies of possible relations of active Hageman factor (HFa) to the problems of thrombolysis. The study is based upon animal experimentation in which 40 normal, 5 dicumarolized and 5 heparinized rabbits each received ellagic acid (Elac 10-2 M) by intravenous continuous infusion at a rate of 1 ml/min for a period of 25 min. The data suggest that the Elac infusion induced in vivo activation of HF. Streptokinase (SK) injection 25 min from the start of Elac i. v. infusion failed to induce clot lysis in blood drawn one min after its injection. The phenomenon was more prominent with low (SK 250 U or 500 U) concentrations of SK. With higher concentrations, SK-induced clot lysis activity was not affected by Elac infusion.In dicumarolized and heparinized rabbits Elac infusion still counteracted the fibrinolysis activating effect of low concentration of SK. The possibility that the above described phenomenon was due to either hypercoagulability or to a non-specific inhibitory effect of Elac upon SK was explored and excluded.It is concluded that HFa and SK have the same site of action. Thus it seems that HFa may block the precursor upon which SK acts by forming a complex with it. It is stressed that activation of this precursor by HFa requires a suitable surface.